AN UNWARRANTED FEAR OF RELIGIOUS SCHOOLING - Kroeker, Frances; Norris, Stephen (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
In this article, we challenge the common liberal assumption that religious schooling undermines the goals of liberal civic education, making it impossible for children to acquire tolerance, critical reasoning skills, or personal autonomy. As a framework for this argument, we respond to some of the claims made by Harry Brighouse in his recent book, School Choice and Social Justice, arguing that the liberal fear of religious schooling, as reiterated by Brighouse, is largely unwarranted. Rather, religious parents and religious schooling can offer children an education that promotes tolerance and critical reflection and that encourages and supports their future autonomy. Key words: school choice, civic education, social justice, liberalism Dans cet article, les auteurs contestent l’hypothèse libérale courante voulant que les écoles confessionnelles nuisent aux buts de l’éducation civique libérale en empêchant les enfants de devenir tolérants, capables de raisonnement critique ou d’autonomie. Dans le cadre de leur argumentation, les auteurs répondent à certaines des affirmations de Harry Brighouse qui, dans un récent ouvrage intitulé School Choice and Social Justice, avance que la peur libérale de l’enseignement religieux est largement injustifiée. Au contraire, les parents qui ont des convictions religieuses et les écoles confessionnelles offrent aux enfants une éducation qui prône la tolérance et la réflexion critique et qui encourage et favorise leur autonomie future. Mots clés : choix d’école, éducation civique, justice sociale, libéralisme